Effect of political decentralization and female leadership on institutional births and child mortality in rural Bihar, India. (July 2017) - Kumar, Santosh; Prakash, Nishith
Abstract: In this paper, we investigate the impacts of political decentralization and women reservation in local governance on institutional births and child mortality in the state of Bihar, India. Using the difference-in-differences methodology, we find a significant positive association between political decentralization and institutional births. We also find that the increased participation of women at local governance led to an increased survival rate of children belonging to richer households. We argue that our results are consistent with female leaders having policy preference for women and child well-being. Highlights: Investigate links between political decentralization, female leadership, and health outcomes in rural Bihar, India. Political decentralization is associated with increased institutional delivery. Political participation of women is associated with reduction in child mortality among richer households. Greater participation of women in local governance can shift society's welfare in an upward direction.